Investigation of Foot Biomechanics in 5-15 Years Old Children Performing Gymnastics - Hamza Sinen; Berkay Üzümcü; Yusuf Yaşasın; Görkem Açar; Sinan Seyhan (Atatürk University, 2024)
Gymnastics is a basic sport branch consisting of eight disciplines and is recommended to be taught to children at an early age. Our study aimed to evaluate the foot biomechanics and static plantar pressure of children aged 5-15 years who were performing rhythmic and artistic gymnastics. The study included 58 (19 Men/39 Women) child gymnasts and aged 5-15 years. Sociodemographic form, static plantar pressure analysis in bipedal position with pedobarography device, hallux valgus angle measurement (HVA), navicular drop test (NDT) and subtalar pronation angle measurement were performed respectively. The measurements were performed in the same way by an experienced expert. IBM Statistical Package for Social Sciences Version 26.0 (SPSS inc, Chicago, IL, USA) statistical programme was used. Tests were analyzed pairwise with Pearson correlation (p ≤ 0.05). The mean age was 7.43±2.37 years, height 124.68±16.97 cm, weight 27.39±11.39 kg and body mass index (BMI) 16.99±3.22 kg/m2. There was no significant difference between weighted and unweighted in NDT results. In pedobarography analysis, hindfoot percentages were higher than forefoot percentages in static bipedal positions. A positive correlation was found between HVA and subtalar angles (p=0.00). In children performing artistic and rhythmic gymnastics, lateral ankle sprain may be observed due to a pronation tendency in subtalar angles. In addition, in the static bipedal position, distortions occurred in the bipedal static force center because the percentage of hindfoot pressure in plantar pressures was higher than the forefoot. Studies with foot-ankle exercises are needed for these.